Problemas de la comunicación literaria. Del sueño de la comunicación al diálogo de sordos - Garayalde, Nicolás (2019)
This article analyzes the notion of literary communication considering old but still valid questions in light of new critical contributions. What problems does the specificity of literary communication pose? Is misunderstanding an inevitable condition of literary communication? How does a written text communicate with the reader? How is the reader able to communicate his reading? What are the consequences regarding literary criticism? To work on this problem, we will follow a path that will halt at the following stops: the dream of communication (Richards), the uninterrupted dialogue (Gadamer and Derrida), and the dialogue of the deaf (Bayard). We will focus especially on the contemporary critic P. Bayard to think of misunderstandingas the basis of communication.